495 Mothers Leading Science: A program to diversify and develop the research workforce. (April 2022) - Lamere, Michelle; Rhode, Sara; Fulkerson, Jayne; Ingbar, David; Hart, Allyson
Abstract : OBJECTIVES/GOALS: The purpose of this group is to foster professional and personal growth as leaders, provide peer mentoring, integrate the roles of scientist, woman, and mother, and build a self-sustaining network of peers for ongoing support throughout their careers in an academic setting. METHODS/STUDY POPULATION: - Study population: 12 Health sciences research faculty (50% protected research time); identify as female; mother of school-age and/or younger children Methods: Year-long program; including a 2-day retreat based on Brene Brown's Dare to Lead RESULTS/ANTICIPATED RESULTS: - Despite the pandemic, 100% of participants continued in the program over the one-year duration and met the attendance requirement of 75% - Screening for burnout was effective - facilitator was able to intervene when severe burnout was noted.